Design, implementation and performance analysis of shunt active filter based on a matrix converter. Issue 3 (4th March 2021) - Tawfiq, Kotb B.; Mansour, Arafa S.; Ibrahim, Mohamed N.; El-Kholy, E. E.; Sergeant, Peter
ABSTRACT: In this paper, a new topology for a shunt active power filter using a matrix converter is proposed. The topology analysis, description of the associated control technique, steady-state and dynamic performance are also presented in this study. The proposed topology does not contain the bulky DC-link capacitor. In addition, the parameters of the proposed filter are robust against the change in the load and the THD percentage is the same under this condition. So, the proposed filter parameters do not require to be retuned with load change. Moreover, a simple and compact form can be realised. The reference currents are calculated using a synchronous reference frame theory. Space vector modulation and hysteresis current control are used to control the rectifier and inverter stages in the indirect matrix converter to obtain the required injected filter current. Finally, a simulation model and an experimental prototype are implemented using Matlab/Simulink program and DSP1104, respectively, with a detailed analysis to the obtained results which confirm the effectiveness and the high accuracy performance of the proposed topology.